A new species of Tremella from India - Thomas, Anjitha; Arun Kumar, T.k. (Phytotaxa, 2023)
A new Tremella species was collected and described from Kerala State, India. Morphological features along with molecular data confirmed the novelty of the species. The new species T. poilkavensis is characterised by amber brown to blackish brown basidiocarp, stalked basidia, conidiospores budding off from basidia, growth on ascomata of Biscogniauxia species and presence of host hyphae within the basidiocarp.